Autophagy and KRT8/keratin 8 protect degeneration of retinal pigment epithelium under oxidative stress. Issue 2 (1st February 2017) - Baek, Ahruem; Yoon, Soojin; Kim, Jean; Baek, Yu Mi; Park, Hanna; Lim, Daehan; Chung, Hyewon; Kim, Dong-Eun
ABSTRACT: Contribution of autophagy and regulation of related proteins to the degeneration of retinal pigment epithelium (RPE) in age-related macular degeneration (AMD) remain unknown. We report that upregulation of KRT8 (keratin 8) as well as its phosphorylation are accompanied with autophagy and attenuated with the inhibition of autophagy in RPE cells under oxidative stress. KRT8 appears to have a dual role in RPE pathophysiology. While increased expression of KRT8 following autophagy provides a cytoprotective role in RPE, phosphorylation of KRT8 induces pathologic epithelial-mesenchymal transition (EMT) of RPE cells under oxidative stress, which is mediated by MAPK1/ERK2 (mitogen-activated protein kinase 1) and MAPK3/ERK1. Inhibition of autophagy further promotes EMT, which can be reversed by inhibition of MAPK. Thus, regulated enhancement of autophagy with concurrent increased expression of KRT8 and the inhibition of KRT8 phosphorylation serve to inhibit oxidative stress-induced EMT of RPE cells as well as to prevent cell death, suggesting that pharmacological manipulation of KRT8 upregulation through autophagy with combined inhibition of the MAPK1/3 pathway may be attractive therapeutic strategies for the treatment of AMD.